1998
DOI: 10.1076/ceyr.17.11.1087.5234
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and its receptor, KDR, following retinal ischemia-reperfusion injury in the rat

Abstract: The hybridization pattern of VEGF and KDR mRNA in the ganglion cell layer strongly suggests that the ganglion cells are the major source of this growth factor. The decrease of VEGF mRNA, KDR/Flk mRNA and VEGF protein levels after ischemia and recovery after reperfusion suggest that transient hypoxia might mediate short-term down-regulation of VEGF and KDR mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
3
9
1
Order By: Relevance
“…Our observation that VEGFR-2 is expressed primarily outside the vasculature in the neonatal retina is in accord with a growing body of evidence showing the importance of VEGF receptors in neural cells (14,(22)(23)(24)(25)(26). Interestingly, this selective localization of VEGFR-2 expression to the neural retina does not persist.…”
Section: Discussionsupporting
confidence: 74%
“…Our observation that VEGFR-2 is expressed primarily outside the vasculature in the neonatal retina is in accord with a growing body of evidence showing the importance of VEGF receptors in neural cells (14,(22)(23)(24)(25)(26). Interestingly, this selective localization of VEGFR-2 expression to the neural retina does not persist.…”
Section: Discussionsupporting
confidence: 74%
“…VEGF is a potent angiogenic factor that regulates both physiological and pathological neovascularization [9,10] secreted from pericytes, retinal endothelial, retinal pigment epithelial, and ganglion cells in response to hypoxia [2,18,19]. In our study, in the I/R injured groups we have also shown that the ischemia has increased the production of VEGF.…”
Section: Discussionsupporting
confidence: 63%
“…To counteract retinal ischemia, the tissue increases the production and release of angiogenic stimulators such as tumor necrosis factor-alpha (TNF-α) and vascular endothelial growth factor (VEGF) in order to promote angiogenesis that is the key event in pathogenesis [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…23 Recently, several studies demonstrated expression of VEGF receptors in retinal ganglion cells, inner nuclear layer, and Mü ller cells. 37,38 Induction of iNOS through VEGF stimulates production of NO from rabbit and human endothelial cells through activation of tyrosine kinases and an increase in intracellular calcium. 18,24,25 Several studies demonstrated that NO plays a critical role in VEGFinduced vascular hyperpermeability and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%